2013
DOI: 10.1371/journal.pone.0068753
|View full text |Cite
|
Sign up to set email alerts
|

miR-379 Regulates Cyclin B1 Expression and Is Decreased in Breast Cancer

Abstract: MicroRNAs are small non-coding RNA molecules that control gene expression post-transcriptionally, and are known to be altered in many diseases including breast cancer. The aim of this study was to determine the relevance of miR-379 in breast cancer. miR-379 expression was quantified in clinical samples including tissues from breast cancer patients (n=103), healthy controls (n=30) and patients with benign breast disease (n=35). The level of miR-379 and its putative target Cyclin B1 were investigated on all brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 30 publications
1
69
0
1
Order By: Relevance
“…For instance, Khan et al . demonstrated that the expression of miR‐379 was significantly reduced in breast cancer, in which this miRNA significantly inhibited cell proliferation by repressing cyclin B1 expression 34. Haenisch et al .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Khan et al . demonstrated that the expression of miR‐379 was significantly reduced in breast cancer, in which this miRNA significantly inhibited cell proliferation by repressing cyclin B1 expression 34. Haenisch et al .…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient tissue was available for pre-post reverse phase proteomics analysis for 18 subjects The most significant changes were reduction in the proliferation associated proteins cyclin B1 (p=0.001) and phosphorylated retinoblastoma protein (p=0.005) [48-50], as well as ribosomal protein S6 (p=0.004), which is correlated with mTOR signaling [51]. All are thought to be important in development of breast cancer [49-51].…”
Section: Resultsmentioning
confidence: 99%
“…One study found that miR-379 levels are lower in circulating blood from patients with atherosclerotic coronary artery disease 18. In cancer studies, miR-379 was found to inhibit breast cancer cell proliferation by regulating cyclin B1 expression;21 Yamamoto reported that miR-379 inhibited cell growth of malignant pleural mesothelioma by targeting interleukin 18 23. In addition, miR-379 also exhibited a tumor-suppressive function in liver cancer 22.…”
Section: Discussionmentioning
confidence: 99%
“…miR-379 has also been found to inhibit cell growth in certain types of cancers including breast cancer, malignant mesothelioma, and liver cancer 212223. In this study, we investigated the functional role of miR-379 in the growth of VSMCs.…”
Section: Introductionmentioning
confidence: 99%